Pre-clinical in vivo Models of Vascular Graft Coating in the Prevention of Vascular Graft Infection: A Systematic Review. (July 2021) - Mufty, Hozan; Van Den Eynde, Jef; Meuris, Bart; Metsemakers, Willem-Jan; Van Wijngaerden, Eric; Vandendriessche, Thomas; Steenackers, Hans P.; Fourneau, Inge
Abstract : Objective: Vascular graft infection (VGI) remains an important complication with a high mortality and morbidity rate. Currently, studies focusing on the role of vascular graft coatings in the prevention of VGI are scarce. Therefore, the aims of this study were to survey and summarise key features of pre-clinical in vivo models that have been used to investigate coating strategies to prevent VGI and to set up an ideal model that can be used in future preclinical research. Data sources: A systematic review was conducted in accordance with the Preferred reporting items for Systematic Reviews and Meta-Analysis guidelines. A comprehensive search was performed in MEDLINE (PubMed), Embase, and Web of Science. Review methods: For each database, a specific search strategy was developed. Quality was assessed with the Toxicological data Reliability Assessment Tool (ToxRTool). The type of animal model, graft, coating, and pathogen were summarised. The outcome assessment in each study was evaluated. Results: In total, 4 667 studies were identified, of which 94 papers focusing on in vivo testing were included. Staphylococcus aureus was the organism most used ( n  = 65; 67.7%). Most of the graft types were polyester grafts. Rifampicin was the most frequently used antibiotic coating ( n  = 43, 48.3%). In the outcome assessment, most studies mentioned colony forming unit count ( n  = 88; 91.7%) and clinical outcome ( n  = 72; 75%). According to the ToxRTool, 21 (22.3%, n  = 21/94) studies were considered to be not reliable. Conclusion: Currently published in vivo models are very miscellaneous. More attention should be paid to the methodology of these pre-clinical reports when transferring novel graft coatings into clinical practice. Variables used in pre-clinical reports (bacterial strain, duration of activity coating) do not correspond well to current clinical studies. Based on the results of this review, a proposal for a complete and comprehensive set up for pre-clinical in vivo testing of anti-infectious properties of vascular graft coatings was defined.